Anuran species abundance in tropical agricultural landscapes - Mohamad Ismail, Siti Wahdaniyah (2018)
The expansion of agricultural crops throughout the tropical region has become the biggest threat to biodiversity. Therefore, study aimed to gain baseline data on anuran abundance in the Malaysian oil palm plantation (OPP) and traditional fruit orchard (TFO). Present study was conducted in Kuala Lumpur Kepong Oil Palm Plantation (OPP) and Kampung Sungai Lalah and Kampong Sungai Batu Traditional Fruit Orchard (TFO), in Pedas, Negeri Sembilan. Data collection was conducted from July till August 2017 and January till February 2018. A total of 40 points were set up in both TFO and OPP with two cycles of observation, giving it a total of 160 observations. The survey design for this research was the systematic point sampling with random start. The survey was conducted during night time, 8.00 p.m to 10.00 p.m where it is the active period for the anurans. Aural and visual search method were used in this study. The result showed the total number of anurans for OPP in both visits are 394 individuals while 290 individuals in TFO. However, analysis indicated that the anuran abundance has no significant difference in both tropical agricultural landscapes. Overall, there were four families of the anuran species recorded in both tropical agricultural landscapes. The four families of anurans consist of Rhacophoridae (Polypedates leucomystax), Microhylidae (Microhyla heymonsii, Microhyla butleri and Kaloula pulchra), Dicroglossidae (Fejervarya limnocharis) and Ranidae (Hylarana glandulosa). These species are typically inhabit disturbed habitats associated with human activities.